Job Insecurity, Debt Burdens and Individual Health - Maite Blázquez Cuesta; Santiago Budría; Ana I. Moro-Egido (Institute of Labor Economics (IZA), 2019)
Job insecurity exerts negative effects on self-reported health. Using the Spanish Survey of Household Finances for 2011-2014, this paper asks whether and to what extent debt burdens enhance these detrimental health effects. To address potential endogeneity problems surrounding this question, the paper adopts Deb and Trivedi's (2006) econometric approach. The results show that the negative effect of job insecurity on self-assessed health is exacerbated if the individual is over-indebted. Moreover, the role of over-indebtedness differs between types of debt, with nonmortgage debts causing larger health losses than mortgage debts. Specifically, the results suggest that being over-indebted with non-mortgage debts boosts the negative impact of job insecurity by a factor of three. Thus, concerns about job insecurity should not be decoupled from concerns about increasing household indebtedness, and policy measures intended to improve individual welfare should consider both phenomena together.
Keywords: G01; I14; I22; 330; self-assessed health; job insecurity; debt burdens